Princípio de ordem no mundo: uma análise dos argumentos dos Diálogos de David Hume - Queiroz, Rafael Gonçalves (2018)
The aim of this study is to analyze the principle of organization of the world, an argument used by the character of Cleanthes in the Dialogues Concerning Natural Religion of David Hume, to try to prove the existence of divine design in the creation and organization of things. In the first chapter, we analyze the argumentation of Cleanthes, Demea, and Philo, characters in the Dialogues Concerning Natural Religion. Demea defends that to prove the existence of God, it is necessary to use a priori arguments, i.e., this would need to be done through formal and deductive arguments. He also defends that it is not possible to know the divine nature, and to try to know it is profanation. Cleanthes takes a different position and affirms that it is possible to prove the existence of God by the a posteriori argument, which would be the argument of design. Thus, he tries to prove that all order in the world is a product of divine planning. The Philo character does not agree with Cleanthes and tries to discredit the hypothesis that Cleanthes defends. In the second chapter, we work with the question of the principle of organization of the universe. Cleanthes proposes the hypothesis that the principle of organization of things arises from the design of an intelligent mind, of a divine nature. Philo, for his part, proposes that the principle of order is intrinsic to matter, i.e., it already has in itself the principle of its organization. In this chapter, we also analyze whether the hypothesis of Philo would be a true alternative to that of Cleanthes. In the third chapter, we examine the analogy made by Cleanthes, namely, that the human mind and ingenuity resemble those of the divine. From this analogy arises the question of anthropomorphism, which is widely criticized by his interlocutors and, for that reason, we also briefly examine this problem and finalize with the change in position of Philo in relation to the argument from design, because he shows signs of agreeing that there is design in relation to the arrangement of things. Due to this change in position, we present an interpretation followed by many commentators of Hume, who defend that the author in fact was using a strategy to avoid censorship at the time in which he changed the position of Philo in relation to the argument from design. After investigation of all the points presented here, we conclude that when we examine the analogy made by Cleanthes, this same analogy served the purpose of proving the existence of God, establishing a similarity between the things created by humans and the ordering of things found in the world created by God. However, as was shown in the last chapter, Cleanthes was not able to uphold his arguments and prove his hypothesis. Consequently, we conclude the study portraying our reading of the Dialogues;it is as if the work had been written with the aim of critiquing the argument from design, in spite of the fact that, at the end of the work, the author led one to believe that he defended that argument through the change in Philo’s position.